Adipose‐derived stem cell spheroids are superior to single‐cell suspensions to improve fat autograft long‐term survival - El Harane, Sanae; Durual, Stéphane; Braschler, Thomas; André‐Lévigne, Dominik; Brembilla, Nicolo; Krause, Karl‐Heinz; Modarressi, Ali; Preynat‐Seauve, Olivier (Journal of cellular and molecular medicine, 2022)
Autologous fat transplantation is a widely used procedure for surgical reconstruction of tissues. The resorption rate of this transplantation remains high and unpredictable, reinforcing the need of adjuvant treatments that increase the long‐term stability of grafts. Adipose‐derived stem cells (ASC) introduced as single cells in fat has been shown clinically to reduce the resorption of fat grafts. On the other hand, the formulation of ASC into cell spheroids results in the enhancement of their regenerative potential. In this study, we developed a novel method to produce highly homogeneous ASC spheroids and characterized their features and efficacy on fat transplantation. Spheroids conserved ASC markers and multipotency. A regenerative gene expression profile was maintained, and genes linked to autophagy were upregulated whereas proliferation was decreased. Their secreted proteome was enriched in comparison with single‐cell ASC suspension. Addition of spheroids to fat graft in an animal model of transplantation resulted in a better graft long‐term stability when compared to single ASC suspension. In conclusion, we provide a novel method to manufacture homogenous ASC spheroids. These ASC spheroids are superior to ASC in single‐cell suspension to improve the stability of fat transplants, reinforcing their potential in reconstructive surgery.